Participatory research in practice: Understandings of power and embodied methodologies. (2nd January 2022) - Hore, Katherine; Gaillard, JC; Davies, Tim; Kearns, Robin
Abstract: Participatory research (PR) has been increasingly used by geographers and other social scientists in recent decades. However, in practice PR often departs from the transformative and empowering characteristics that define it. This article uses candid reflections on the first author's attempt at PR to highlight areas where the under‐theorisation of the complexities of fieldwork and the co‐constitutive nature of research and emotions could be contributing to such depoliticised practice. Some problematic aspects of how power is understood in PR are also discussed, echoing the call from proponents of participation at large for more coherent frameworks to understand power relations.